Development of subcarrier multiplexing SAC-OCDMA system based on free space optics - Hussein Saad Mohammed (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
The results presented in this research are based on the simulation "optisystem" ver.7 in terms of the number of simultaneous users, effective power, data rate, specific attenuations, distance, and BER, exhibiting the ability of the proposed system as a powerful technique for future access network. Thus, this system is a potential candidate for future broadband access solutions in communication networks. The SAC-OCDMA FSO using SCM system shows better performance compared with the conventional SAC-OCDMA FSO system and the number of user improves by 31.8%.